1979
DOI: 10.1259/0007-1285-52-616-308
|View full text |Cite
|
Sign up to set email alerts
|

Induced thermal resistance in the mouse ear

Abstract: The mouse ear (pinna) was used to investigate the effect of two hyperthermic treatments. Heating was by immersion in hot water at 43.5 degrees C. A single treatment of about 50 minutes was required to cause necrosis in 50% of the ears heated. When heat treatment was given in two equal fractions the total heating time had to be increased if the interval between fractions was greater than four hours. By 24 hours a total treatment of about 100 minutes was required, indicating almost complete recovery from the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…Both the fractionation interval necessary to obtain maximum thermotolerance increased as the preheating time was increased. This agrees with earlier observations on cell cultures in vitro (Gerner et al, 1976;Li et al, 1982;Nielsen & Overgaard, in press, and on different normal tissues in vivo (Law et al, 1979;Hume & Marigold, 1980;Urano et al, 1980;Rice et al, 1982;Field & Anderson, in press). Recently, studies on solid tumours have also shown that at a given interval the degree of thermotolerance increased as the preheating time was increased (Maher et al, 1981;.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Both the fractionation interval necessary to obtain maximum thermotolerance increased as the preheating time was increased. This agrees with earlier observations on cell cultures in vitro (Gerner et al, 1976;Li et al, 1982;Nielsen & Overgaard, in press, and on different normal tissues in vivo (Law et al, 1979;Hume & Marigold, 1980;Urano et al, 1980;Rice et al, 1982;Field & Anderson, in press). Recently, studies on solid tumours have also shown that at a given interval the degree of thermotolerance increased as the preheating time was increased (Maher et al, 1981;.…”
Section: Discussionsupporting
confidence: 92%
“…Such a delay period was not observed in the present study. The time for loss of thermotolerance clearly depended on the preheating time as also demonstrated on normal tissues in vivo (Law et al, 1979;Hume & Marigold, 1980 (Figs 7 and 8). A similar relationship has also been demonstrated for cell cultures (Henle et al, 1979;Nielsen & Overgaard, in press).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Further results of Miyakoshi et al (1979) showed that radiosensitization was diminished if low temperature hyperthermia (42.0°C) preceded high temperature hyperthermia at 45.0°C causing thermotolerance. Results from normal tissue studies in vivo also show that a conditioning heat treatment given at various times before subsequent heating and irradiation could result in thermal tolerance and reduced TERs (Henle 1982, Law et al, 1979a,b, Dethlefsen and Dewey 1982. In these studies it was shown that the reduction in TERs was not temporally related to the onset of thermal tolerance (Marigold and Hume, 1982;Law et al, 1979a,b).…”
Section: Discussionmentioning
confidence: 99%